Analisis Kinerja Keuangan Perusahaan PT Indofood Cbp Sukses Makmur Tbk Sebelum dan Sesudah Akuisisi - Ratih Mustika Sari; Tika Dwi Prasasti; Endang Kartini Panggiarti (Universitas 45 Surabaya, 2023)
This study was designed with the aim of digging up information on whether a company merger can be profitable and whether there are differences in the financial results of PT. Indofood Sukses Makmur uses liquidity (CR, QR), leverage (DER, DAR) and profitability (ROI, ROE). The method used in this study is a non-causal comparative method because it serves to provide an overview of the analysis of the relationship between status before and after the acquisition. The comparative non-causal method also provides information about the parameters and differences of several variables used in the research object through hypothesis testing. This research was conducted using quantitative descriptive analysis techniques and statistical tests (Paired Sample T-Test) to determine financial efficiency in companies PT. Indofood Sukses Makmur before and after the acquisition is based on a descriptive analysis method that varies up or down. The average ratio of changes experienced by the PT before the acquisition and after the acquisition. The company PT.Indofood Sukses Makmur's liquidity (CR and QR), profitability (ROI and ROE) and debt (DER and DAR) decreased.